Empowering Children as Agents of Climate Resilience: Integrating Education for SDG 13 - Ab Rahman Nurul Hidayat; Rosli Yanti (E3S Web of Conferences)
As the world faces the challenges of climate change, its extensive effects are experienced in many areas of human life, emphasizing the urgent need to acknowledge its frequently overlooked consequences on the most susceptible individuals, particularly children. This study examines the Convention on the Rights of the Child (CRC), which provides detailed guidelines on children’s rights in this challenge, aligning with the Sustainable Development Goal (SDG) 13. Furthermore, this research emphasizes the pivotal role of children as agents of change, particularly through the integration of education as outlined in Target 13.3. Grounded in socio-legal research conducted qualitatively, all data were meticulously gathered through library research and subjected to thorough analysis using the content analysis method. The paramount considerations revolve around the child’s best interests and developmental rights. The study affirms that children have the rights to a healthy environment, education, and participation in addressing climate change. However, their limited awareness hinders their ability to participate effectively, leaving them vulnerable and unprepared for the future. These findings underscore the imperative of taking proactive measures such as incorporating Education for Sustainable Development (ESD) into school curricula, involving children in decision-making processes, and fostering awareness of sustainable living practices.